MANAJEMEN PEMBELAJARAN TEACHING FACTORY BERBASIS ENTREPRENEURSHIP - Triyanto, Joko; Siraj, Siraj; Bahri, Saiful (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The objectives of this research are (1) to understand the management of teaching factory learning which includes planning, implementation and evaluation in realizing an entrepreneurial spirit for students; (2) knowing the supporting and inhibiting factors and their solutions; (3) knowing the results of teaching factory learning management in realizing students' entrepreneurial spirit. This research is qualitative research whose data collection techniques include interviews, observation and documentation. The results of this research are (1) teaching factory learning management can be seen in planning that has been carried out well, organization that is structured and carried out well, implementation according to industry standards, evaluation of learning achievement analysis; (2) the supporting factors in teaching factory learning are infrastructure according to industry standards and competent teachers, the inhibiting factors are the planning time not matching the implementation, and there are not many industries collaborating to carry out teaching factory learning, while the solution is to make a schedule block and increase cooperation with related industries; (3) the results of the teaching factory learning management show that the teaching factory learning management is running well and can realize the entrepreneurial spirit of students.